HUBUNGAN GAYA KEPEMIMPINAN KEPALA RUANG DENGAN KEPUASAN KERJA PERAWAT PELAKSANA DI RS PANTI WALUYO SAWAHAN MALANG - Rini Roostyowati (Universitas Tribhuwana Tunggadewi, 2015)
Style of leadership is a process conducted by managers to direct and influence subordinates, that the subordinates were willing to move all of his abilities. Consists of autocratic, democratic, participatory, free acts. Job satisfaction is an emotional response to various aspects of the work of nurses, while on duty in the inpatient unit, divided into two categories, namely satisfied and dissatisfied. The purpose of this study to identify leadership styles relationship with job satisfaction room nurses at Hospital Panti Waluya Sawahan Malang. This study used a cross-sectional study. Sampling technique used is proportional random sampling, the sample number 52 nurses. The technique of data analysis using Spearman Rank. Results of univariate analysis showed that the autocratic leadership style head space 0%, 59.6% democratic, participatory 28.9%, 11.5% free acts. on job satisfaction of nurses 86.5% satisfied, and 13.5% are not satisfied. Bivariate analysis showed that there is a relationship of space leadership style and job satisfaction of nurses in Hospital Panti Waluya Sawahan Malang with p = 0.000. Suggestions for head space for not using free leadership style offense for nurses to provide optimum service without feeling left